Second molar morphology in relation to third molar agenesis - Macatangay, Cecile C.
This seminar paper deals with one product of the modernization of man, the agenesis of the human third molar. It is the objective here whether the second molar morphology as determined by cusp number is related to third molar agenesis and whether a relationship exists between third molar agenesis and the presence of other congenitally missing teeth. Out of the 203 dental students in the UPCD, 37 had agenesis of one or more of the third molars, further studied was the relationship between third molar agenesis and molar cusp number variability. Intraoral roentgenographic x-rays were taken to confirm the absence or presence of third molar agenesis. Utilizing good artificial illumination mouth mirror and explorer a thorough oral examination was conducted to determine the morphology of the second molars as well as to establish the possibility of other congenitally missing teeth. It showed that a great percentage of the second molars exhibited the 4 cusp type for both the maxilla and the mandible, In the congenital absence of the third molars, there is a notable increase in the percentage of second molars exhibiting 3 cusps especially among the females. In the mandible absence or presence of third molars do not seem to affect the number of cusps of the M2's. Congenitally missing teeth of other morphologic classes may be associated with M3 agenesis.